EKONOMI REHABILITASI DAERAH TANGKAPAN WADUK (Rehabilitation Economic of Dam Catchment Area) - Soedarsono Soedomo (Media Konservasi, 2005)
Dynamic optimization approach is employed in this paper. Moreover, in this paper it is indicated that not all crititcal lands in the catchment areas of a dam need to be rehabilitated even though opportunity for the critical lands up to the end life of the dam is available. Budget allocation for rehabilitating catchment areas need to consider this factor to avoid inefficiency. Too large catchment areas can create an inefficiency. Location selection for developing a dam needs to take into account the costs of conservation and/or rehabiltation of catchment areas.